2020
DOI: 10.2147/dmso.s232133
|View full text |Cite
|
Sign up to set email alerts
|

<p>Chaperone-Based Therapeutic Target Innovation: Heat Shock Protein 70 (HSP70) for Type 2 Diabetes Mellitus</p>

Abstract: Type 2 diabetes mellitus (T2DM) is still a global health problem. Current T2DM treatments are limited to curing the symptoms and have not been able to restore insulin sensitivity in insulin-sensitive tissues that have become resistant. In the past decade, some studies have shown the significant role of a chaperone family, heat shock protein 70 (HSP70), in insulin resistance pathogenesis that leads to T2DM. HSP70 is a cytoprotective molecular chaperone that functions in protein folding and degradation. In gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 65 publications
1
23
0
3
Order By: Relevance
“…However, the inhibition of cholinesterase itself cannot explain for the wide range of disorders, especially in the case of chronic exposure in subclinical dose [7], [18]. Based on those mentioned above, several biomarkers have been elucidated to determine the effect of organophosphate on health, risk of malignancy, and metabolic diseases [22], [23], [24]. So that, the recent studies start to shift focus on other long-term effects of the pesticide such as the oxidative stress as well as the cholinesterase activity among farmers who are more vulnerable to the daily-pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibition of cholinesterase itself cannot explain for the wide range of disorders, especially in the case of chronic exposure in subclinical dose [7], [18]. Based on those mentioned above, several biomarkers have been elucidated to determine the effect of organophosphate on health, risk of malignancy, and metabolic diseases [22], [23], [24]. So that, the recent studies start to shift focus on other long-term effects of the pesticide such as the oxidative stress as well as the cholinesterase activity among farmers who are more vulnerable to the daily-pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%
“…3 That is, the number of DM will continue to rise due to the increasing ageing population and prevalence of rising obesity, recognised as a global public health issue challenge of the 21st century across the world. 4 5 …”
Section: Introductionmentioning
confidence: 99%
“…Songsasen and Collado-Fernandez et al reported that energy metabolism is essential for oocyte maturation because it requires a lot of energy from various substrates, including carbohydrates, amino acids, and lipids [18], [19]. The mitochondrial apoptosis showed that mitochondria as energy producers from various substrates were not able to produce energy for the oocyte maturation [20], [21].…”
Section: Association Of Cytochrome C Levels With Mitochondrial Apoptomentioning
confidence: 99%